Secretos de encierro: somos mujer palabra (2021)
What does it mean to be a woman locked up? What happens when you don?t leave a place for a long period of time? What do you hear? What is woven in there? Secretos de Encierro, Locked Down Secrets, is a project that arises from the remote encounter with a Wayuu woman called Adeinis Boscán. Starting from the ritual of the Encierro, a transformation period for girls in the indigenous community settled in La Guajira, Colombia, the project wonders about the construction of female narratives in the domestic space. Through a series of long-distance dialogues that took place during a mandatory confinement, the authors wondered about the meanings of their encounter: two women from different cultures and territories who connected finding similarities in their ancestors, their weaves, their words, their everyday life locked up. It is a project that seeks to create narratives claiming female authorship, a textile library that seeks...